2014
DOI: 10.1534/genetics.114.165423
|View full text |Cite
|
Sign up to set email alerts
|

The “Domestication Syndrome” in Mammals: A Unified Explanation Based on Neural Crest Cell Behavior and Genetics

Abstract: Charles Darwin, while trying to devise a general theory of heredity from the observations of animal and plant breeders, discovered that domesticated mammals possess a distinctive and unusual suite of heritable traits not seen in their wild progenitors. Some of these traits also appear in domesticated birds and fish. The origin of Darwin’s “domestication syndrome” has remained a conundrum for more than 140 years. Most explanations focus on particular traits, while neglecting others, or on the possible selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
844
5
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 588 publications
(888 citation statements)
references
References 92 publications
28
844
5
11
Order By: Relevance
“…Wilkins et al (2014) proposed that all the "phenes" (single phenotypic traits) of the DS might be explained by relatively small deficits of neural crest cells in their final locations -relative to the progenitor wild breeds -after these cells have migrated in early embryonic development from the dorsal side of the neural tube. In this view, selection for docility and tameness -presumably the initial step in domestication -entails selection for those properties produced as a consequence of mild neural crest cell deficiencies in development.…”
Section: Two Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…Wilkins et al (2014) proposed that all the "phenes" (single phenotypic traits) of the DS might be explained by relatively small deficits of neural crest cells in their final locations -relative to the progenitor wild breeds -after these cells have migrated in early embryonic development from the dorsal side of the neural tube. In this view, selection for docility and tameness -presumably the initial step in domestication -entails selection for those properties produced as a consequence of mild neural crest cell deficiencies in development.…”
Section: Two Hypothesesmentioning
confidence: 99%
“…In this view, selection for docility and tameness -presumably the initial step in domestication -entails selection for those properties produced as a consequence of mild neural crest cell deficiencies in development. They further suggested that docility in the early stages of domestication specifically reflected smaller adrenal glands (which derive in part from neural crest cells) producing lower concentrations of adrenocorticotropic hormones, leading to delayed and/or reduced "fight-or-flight" responses (Wilkins et al, 2014). (Domesticated rats and foxes, in fact, have smaller adrenal glands than their wild counterparts and produce lower concentrations of adrenocorticotropic hormones.)…”
Section: Two Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Behavioral differences observed include more tame and docile individuals, with lower fearfulness. Physiological changes are also present, including an attenuated physiological stress response and altered reproduction cycles (Wilkins et al, 2014).…”
Section: Introduction Domesticationmentioning
confidence: 99%